The complete mitochondrial genome of the edible mushroom Grifola frondosa. Issue 1 (2nd January 2022) - Song, Ying; Wan, Jianing; Shang, Jun-Jun; Feng, Zhan; Jin, Yuchang; Li, Hewen; Guo, Ting; Wu, Ying-Ying; Bao, Da-Peng; Zhang, Min; Lv, Litao; Liu, Junjie; et al.
Abstract: The culinary-medicinal mushroom Grifola frondosa is widely cultivated in East Asia. In this study, the complete mitochondrial genome of G. frondosa was determined using Illumina sequencing. The circular molecule was 197, 486 bp in length with a content of 25.01% GC, which was one of the largest mitochondrial genomes in the order Polyporales. A total of 39 known genes encoding 13 common mitochondrial genes, 24 tRNA genes, 1 ribosomal protein s3 gene ( rps3 ), and 1 DNA polymerase gene ( dpo ) were predicted in this genome. The phylogenetic analysis showed that G. frondosa clustered together with Sparassis crispa, Laetiporus sulphureus, Wolfiporia cocos, and Taiwanofungus camphoratus . The complete mitochondrial genome reported here may provide new insight into genetic information and evolution for further studies.